EXPORT ANALYSIS: AUTHORITY OF INFLATION AND EXCHANGE RATE IN ASEAN-8 - Rika Mauliana; Abd. Jamal; Suriani Suriani (TRIKONOMIKA, 2020)
This study was aimed to analyze the relationship of long-term and short-term equilibrium between exchange rates and inflation on exports in ASEAN-8 countries (Brunei Darussalam, Laos, Indonesia, Malaysia, Singapore, Philippines, Vietnam and Thailand) by using analysis model with the Autoregressive Distributed Lag (ARDL) panel from the period 1990 to 2017. The model selection was based on long-term and short-term capabilities with different stationary levels. The results revealed that in long-term the exchange rate and inflation had a dominant influence on export activities in ASEAN-8 countries, while inflation had a dominant influence on exports in short-term. This result proved that inflation had a large influence on the growth of the trade stability, if the cost of products and services continuously increased in the market mechanism, it will result in the increased public consumption. The excess liquidity in the market triggered the consumption or speculation which resulted in the non-compliance products distribution and the decline in currency value continuously.